Magnetic wedge and rotating electrical machine

By using a magnetic wedge composed of a plurality of flat magnetic metal particles and inclusion phases and forming a surface coating on its surface, the existing magnetic wedge is solved and the problem of inefficiency in a rotating motor is achieved, achieving higher efficiency and performance.

CN119675309APending Publication Date: 2025-03-21KK TOSHIBA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410534687.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-21
Filing Date
2024-04-30
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing magnetic wedges have problems such as low saturation magnetization, low magnetic permeability, large loss, and insufficient thermal stability and mechanical characteristics in improving the efficiency of rotating motors.

Method used

A magnetic wedge composed of a plurality of flat magnetic metal particles and inclusion phases is used, and a surface coating is formed on its surface to improve the electrical, magnetic and thermal mechanical characteristics of the magnetic wedge.

Benefits of technology

The excellent electrical characteristics, heat resistance and mechanical characteristics of the magnetic wedge are realized, and the efficiency and performance of the rotating motor are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119675309A_ABST
    Figure CN119675309A_ABST
Patent Text Reader

Abstract

A magnetic wedge according to the present embodiment is a magnetic wedge for a rotating electrical machine, the magnetic wedge comprising a plurality of flat magnetic metal particles and an inclusion phase, and a surface coating layer being present on at least a portion of the surface of the magnetic wedge.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Citation of Related Applications

[0002] This application is based on Japanese Patent Application No. 2023-156245 (filing date: September 21, 2023), and claims priority based on the patent application. The present application incorporates the entire contents of the application by reference. Technical Field

[0003] Embodiments of the present invention relate to a magnetic wedge and a rotating electric machine. Background Art

[0004] Generally, the coil winding of a rotating electric machine is accommodated in the core slot and supported and fixed by a wedge-shaped piece provided at the slot opening. The material of the wedge-shaped piece is generally a non-magnetic body, but since the magnetic resistance value in the gap between the stator core and the rotor core becomes discontinuous, the magnetic flux distribution of the core surface portion opposite to the wedge-shaped piece across the gap pulsates, and the high-order harmonic loss increases. In order to reduce the high-order harmonic loss, a wedge-shaped piece (magnetic wedge) with moderate magnetism has been provided in the past. By applying the magnetic wedge, the high-order harmonic loss is reduced and the efficiency of the rotating electric machine is improved. Figure 1 It is a schematic diagram of the use state of the magnetic wedge and the effect of the magnetic wedge. Figure 1 An example of a radial gap type rotating electrical machine is shown. Figure 1 The magnetic wedge 100 , the coil 230 , the core teeth 250 , and the core slots 260 are described.

[0005] Regarding the magnetic wedge, it is self-evident that the higher the magnetic permeability of the magnetic wedge, the more it can reduce the high-order harmonic loss. Figure 1 As shown, since the magnetic wedge is configured in a manner that bridges the adjacent core teeth, there is a disadvantage that the leakage flux flowing through the core teeth through the magnetic wedge will increase. In addition, the existing magnetic wedge is prone to magnetic saturation due to its low saturation magnetization, and the efficiency improvement of the rotating motor is limited due to the large loss (large hysteresis loss due to high coercive force, and large eddy current loss due to low resistivity). In addition, the existing magnetic wedge has a low magnetic permeability, so the efficiency improvement of the rotating motor is limited, and it is insufficient in terms of thermal stability and mechanical properties (strength, toughness). Therefore, it is desired to improve the characteristics of the magnetic wedge in terms of saturation magnetization, magnetic permeability, loss, strength, toughness, etc. In particular, it is desired to improve the magnetic properties, electrical properties, and thermomechanical properties of the magnetic wedge. Summary of the invention

[0006] An object of the present invention is to provide a magnetic wedge and a rotating electric machine having excellent electrical characteristics and heat resistance (electrical characteristics, magnetic characteristics, and mechanical characteristics).

[0007] The magnetic wedge according to the embodiment is a magnetic wedge for a rotary electric machine. The magnetic wedge includes a plurality of flat magnetic metal particles and an inclusion phase, and a surface coating layer exists on at least a portion of the surface of the magnetic wedge.

[0008] According to the above aspects, a magnetic wedge and a rotating electrical machine having excellent electrical characteristics and heat resistance (electrical characteristics, magnetic characteristics, and mechanical characteristics) are provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 It is a schematic diagram of the use state of the magnetic wedge and the effect of the magnetic wedge.

[0010] Figure 2A-2B This is a schematic diagram of flat magnetic metal particles in the magnetic wedge according to the first embodiment.

[0011] Figure 3 This is a conceptual diagram showing an example of a method of determining the thickness of the flat magnetic metal particles in the magnetic wedge according to the first embodiment.

[0012] Figure 4A-4C This is a conceptual diagram for explaining a method of obtaining the maximum length and the minimum length within the flat surface of the flat magnetic metal particles in the magnetic wedge according to the first embodiment.

[0013] Figure 5 A conceptual diagram for explaining another example of how to obtain the maximum length and the minimum length within the flat surface of the flat magnetic metal particles in the magnetic wedge according to the first embodiment.

[0014] Figure 6 This is a schematic diagram showing the direction in which the coercive force is measured by changing the direction at intervals of 22.5 degrees with respect to the 360-degree angle within the flat surface of the flat magnetic metal particle in the magnetic wedge of the first embodiment.

[0015] Figure 7 It is a schematic diagram of the magnetic wedge according to the first embodiment.

[0016] Figure 8 It is a schematic diagram of the magnetic wedge according to the first embodiment.

[0017] Fig. 9 This is another schematic diagram of the magnetic wedge according to the first embodiment.

[0018] Fig.10 This is a schematic diagram showing an example of a radial gap type rotating electrical machine according to the second embodiment.

[0019] Fig.11 This is a schematic diagram showing an example of an axial gap type rotating electrical machine according to the second embodiment.

[0020] Fig.12This is a schematic diagram showing an example of a generator according to the second embodiment.

[0021] Fig.13 This is a schematic diagram showing an example of a linear motor according to a second embodiment.

[0022] Explanation of symbols

[0023] 6: Flat surface

[0024] 9: Coating layer

[0025] 10: Flat magnetic metal particles

[0026] 20: Inclusion phase

[0027] 100: Magnetic wedge

[0028] 200: Rotating motor

[0029] 210: Rotor

[0030] 220: Stator

[0031] 222: Stator core

[0032] 230: Coil

[0033] 232: Excitation coil

[0034] 234: Armature coil

[0035] 240: Gap surface

[0036] 250: Core teeth

[0037] 260: Core slot

[0038] 270: Stator

[0039] 280: Axis

[0040] 290: Active Components DETAILED DESCRIPTION

[0041] Hereinafter, the embodiments will be described using the drawings. It should be noted that the same or similar reference numerals are used to designate the same or similar parts in the drawings. In addition, in this specification, all measurements are performed at 25° C. unless otherwise specified.

[0042] In this specification, each direction of "axial direction", "rotational direction" and "radial direction" is defined based on the rotor of the rotating electrical machine. That is, "axial direction" means the direction along the rotation axis of the rotor, and "rotational direction" means the circumferential direction around the rotation axis of the rotor (or its tangential direction). And, "radial direction" means the direction orthogonal to (perpendicularly intersecting) the rotation axis of the rotor.

[0043] (First embodiment)

[0044] The magnetic wedge according to the embodiment is a magnetic wedge for a rotary electric machine. The magnetic wedge includes a plurality of flat magnetic metal particles and an inclusion phase, and a surface coating layer exists on at least a portion of the surface of the magnetic wedge.

[0045] Flat magnetic metal particles are flat particles (flaky particle, flattened particle) in a flaky (flaky, flattened) shape (flaky shape, flattened shape). It should be noted that the flat magnetic metal particles can also be replaced by magnetic metal particles of all shapes other than flat. The magnetic wedge of this embodiment exerts its effect by covering at least a portion of the surface of the magnetic wedge with a surface coating layer. Therefore, magnetic metal particles in shapes other than flat can also exert excellent magnetic properties, electrical properties, and thermomechanical properties. In particular, in the case of a flat shape, it can be expected that more excellent magnetic properties, electrical properties, and thermomechanical properties will be improved.

[0046] Fig. 2 is a schematic diagram of the flat magnetic metal particles in the magnetic wedge according to the first embodiment, showing the coating layer 9 and the flat magnetic metal particles 10.

[0047] The coating layer more preferably includes at least one non-magnetic metal selected from the group consisting of Mg, Al, Si, Ca, Zr, Ti, Hf, Zn, Mn, Ba, Sr, Cr, Mo, Ag, Ga, Sc, V, Y, Nb, Pb, Cu, In, Sn, and rare earth elements, and includes at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N), and fluorine (F).

[0048] As the non-magnetic metal, Al and Si are particularly preferred from the viewpoint of thermal stability. When the flat magnetic metal particles contain at least one non-magnetic metal selected from the group consisting of Mg, Al, Si, Ca, Zr, Ti, Hf, Zn, Mn, Ba, Sr, Cr, Mo, Ag, Ga, Sc, V, Y, Nb, Pb, Cu, In, Sn, and rare earth elements, the coating layer more preferably contains at least one non-magnetic metal that is the same as the non-magnetic metal that is one of the constituent components of the flat magnetic metal particles.

[0049] Among oxygen (O), carbon (C), nitrogen (N) and fluorine (F), oxygen (O) is preferably contained, and an oxide or a composite oxide is preferred.

[0050] The above is from the perspective of the ease of forming the coating layer, oxidation resistance, and thermal stability. Through the above method, the adhesion between the flat magnetic metal particles and the coating layer can be improved, and the thermal stability and oxidation resistance of the magnetic wedge described later can be improved. The coating layer can not only improve the thermal stability and oxidation resistance of the flat magnetic metal particles, but also improve the resistance of the flat magnetic metal particles. By improving the resistance, eddy current loss can be suppressed and the frequency characteristics of magnetic permeability can be improved. Therefore, the coating layer is preferably high in resistance, for example, preferably has a resistance value of 1 mΩ·cm or more.

[0051] In addition, the presence of a coating layer is also preferred from a magnetic point of view. Flat magnetic metal particles can be regarded as approximate thin films because their thickness is relatively small relative to the size of the flat surface. At this time, the structure obtained by forming a coating layer on the surface of the flat magnetic metal particles for integration can be regarded as an approximate stacked film structure, so the magnetic domain structure is energetically stabilized. As a result, the coercive force can be reduced, thereby reducing the hysteresis loss, which is preferred. At this time, the magnetic permeability also becomes larger, which is preferred. From this point of view, since the magnetic domain structure becomes easy to stabilize, the coating layer is more preferably non-magnetic.

[0052] The thickness of the coating layer is preferably 0.1 nm or more and 1 μm or less. By setting the thickness range, it is possible to have appropriate thermal stability, oxidation resistance, and electrical resistance, and the saturation magnetization is not made too small, thereby suppressing the reduction of magnetic permeability. In addition, from the perspective of magnetism, the effects of stabilizing the magnetic domain structure and reducing coercivity, reducing loss, and increasing magnetic permeability are not impaired. The thickness of the coating layer is more preferably 0.1 nm or more and 100 nm or less.

[0053] The thickness of the flat magnetic metal particle refers to the average thickness of one flat magnetic metal particle. The method for obtaining the thickness is not limited as long as it is a method that can obtain the average thickness of one flat magnetic metal particle.

[0054] For example, the following method can be used: observe the cross-section of the flat magnetic metal particle perpendicular to its flat surface using a transmission electron microscope (TEM) or a scanning electron microscope (SEM) or an optical microscope, select any 10 or more points along the direction within the flat surface in the cross-section of the observed flat magnetic metal particle, measure the thickness of each selected point, and use the average value.

[0055] In addition, the following method can also be used: in the cross-section of the observed flat magnetic metal particle, select more than 10 points at equal intervals from the end toward the other end in the direction within the flat surface (in this case, the end and the other end are special positions and it is preferably not selected), measure the thickness of each selected point, and use the average value.

[0056] Figure 3 This is a conceptual diagram showing an example of a method of determining the thickness of the flat magnetic metal particles in the magnetic wedge according to the first embodiment. Figure 3 The method for calculating the thickness in this case is specifically shown. Select 10 locations (excluding the end) at equal intervals from one end toward the other end in the direction within the flat surface, and let the thickness of each location be t 1 ,t 2 ,……,t 10 In the case of 1 +t 2 +……+t 10 ) / 10. It should be noted that it is preferable to measure as many positions as possible during the measurement in order to obtain average information. It should be noted that when the contour line of the cross section has a severely uneven or rough surface and it is difficult to obtain the average thickness while maintaining the original state, it is preferable to smooth the contour line with an average straight line or curve according to the situation before performing the above method.

[0057] The average thickness refers to the average value of the thicknesses of a plurality of flat magnetic metal particles, and is distinguished from the simple “thickness” mentioned above.

[0058] When calculating the average thickness, it is preferred to use a value obtained by averaging 20 or more flat magnetic metal particles. In addition, it is preferred to calculate the average thickness using as many flat magnetic metal particles as possible as an object, because average information can be obtained. In addition, when it is not possible to observe 20 or more flat magnetic metal particles, it is preferred to observe as many flat magnetic metal particles as possible and use the value obtained by averaging them.

[0059] The average thickness of the flat magnetic metal particles is preferably greater than 10 nm and less than 100 μm. More preferably, it is greater than 10 nm and less than 1 μm, and further preferably greater than 10 nm and less than 100 nm. In addition, the flat magnetic metal particles preferably include particles having a thickness of greater than 10 nm and less than 100 μm, more preferably greater than 10 nm and less than 1 μm, and further preferably greater than 10 nm and less than 100 nm. Through these, when a magnetic field is applied in a direction parallel to the flat surface, eddy current losses can be sufficiently reduced, which is preferred. In addition, when the thickness is small, the magnetic moment is confined to a direction parallel to the flat surface, and it is easy to magnetize with rotational magnetization, which is preferred. In the case of magnetization with rotational magnetization, it is easy to reversibly magnetize, so the coercive force becomes smaller, thereby reducing hysteresis losses, which is preferred.

[0060] The average length of the flat magnetic metal particles is defined as (a+b) / 2 using the maximum length a and the minimum length b within the flat surface. The maximum length a and the minimum length b can be obtained by the following operation. For example, think of the rectangle with the smallest area among the rectangles circumscribed to the flat surface. Then, the length of the long side of the rectangle is set as the maximum length a, and the length of the short side is set as the minimum length b.

[0061] FIG4 is a conceptual diagram for explaining a method for obtaining the maximum length and the minimum length within the flat surface of the flat magnetic metal particles in the magnetic wedge of the first embodiment. FIG4 is a schematic diagram showing the maximum length a and the minimum length b obtained by the above method using several types of flat magnetic metal particles as examples. The maximum length a and the minimum length b can be obtained by observing the flat magnetic metal particles using a TEM, SEM, or optical microscope, as with the average thickness.

[0062] In addition, image analysis of the microscope photograph can also be performed on a computer to obtain the maximum length a and the minimum length b. In either case, it is preferred to obtain the maximum length a and the minimum length b using 20 or more flat magnetic metal particles as the object. In addition, it is preferred to obtain the average information using as many flat magnetic metal particles as possible.

[0063] In addition, when more than 20 flat magnetic metal particles cannot be observed, it is preferred to observe as many flat magnetic metal particles as possible and adopt the value obtained by averaging them. In addition, it is preferred to obtain the value as average as possible at this time, so it is preferred to observe or image analyze in a state where the flat magnetic metal particles are uniformly dispersed (in a state where a plurality of flat magnetic metal particles with different maximum lengths and minimum lengths are dispersed as randomly as possible). For example, it is preferred to observe or image analyze by sticking a plurality of flat magnetic metal particles on a tape while fully stirring and mixing them, or by dropping a plurality of flat magnetic metal particles from top to bottom and sticking them on a tape.

[0064] However, depending on the flat magnetic metal particles, when the maximum length a and the minimum length b are obtained by the above method, there is a possibility that the method cannot grasp the essence. Figure 5 This is a conceptual diagram for explaining another example of a method for obtaining the maximum length and the minimum length within the flat surface of the flat magnetic metal particles in the magnetic wedge of the first embodiment.

[0065] For example, in Figure 5 In this case, the flat magnetic metal particles are in an elongated and curved state. In this case, the maximum length and the minimum length of the flat magnetic metal particles are essentially Figure 5 The lengths of a and b shown. Thus, the method for finding the maximum lengths a and b is not completely uniquely determined. Basically, there is no problem with the method of "thinking of the rectangle with the smallest area among the rectangles circumscribed to the flat surface, and setting the length of the long side of the rectangle as the maximum length a, and setting the length of the short side as the minimum length b". However, depending on the shape of the particles, when this method cannot grasp the essence, the maximum length a and minimum length b that grasp the essence are calculated according to circumstances. The thickness t is defined as the length in the direction perpendicular to the flat surface. The ratio A of the average length within the flat surface to the thickness is defined as A = ((a+b) / 2) / t) using the maximum length a, the minimum length b, and the thickness t.

[0066] The average value of the ratio of the average length in the flat surface of the flat magnetic metal particles to the thickness is preferably 5 or more and 10000 or less. This is because the magnetic permeability is increased and the ferromagnetic resonance frequency can be increased, thereby reducing the ferromagnetic resonance loss.

[0067] The average value is used for the ratio of the average length in the flat surface to the thickness. Preferably, the value obtained by averaging more than 20 flat magnetic metal particles is preferably used. In addition, it is preferred to use as many flat magnetic metal particles as possible as the object to obtain the information that can be averaged. In addition, when it is not possible to observe more than 20 flat magnetic metal particles, it is preferred to observe as many flat magnetic metal particles as possible and use the value obtained by averaging them. It should be noted that, for example, when there are particles Pa, particles Pb, particles Pc, each with a thickness of Ta, Tb, Tc, and an average length in the flat surface of La, Lb, Lc, the average thickness is calculated by (Ta+Tb+Tc) / 3, and the average value of the ratio of the average length in the flat surface to the thickness is calculated by (La / Ta+Lb / Tb+Lc / Tc) / 3.

[0068] The flat magnetic metal particles preferably have a coercivity difference based on direction within the flat surface. The larger the ratio of the coercivity difference based on direction, the more preferred it is, preferably 1% or more. More preferably, the ratio of the coercivity difference is 10% or more, further preferably, the ratio of the coercivity difference is 50% or more, and further preferably, the ratio of the coercivity difference is 100% or more.

[0069] The ratio of the coercive force difference mentioned here refers to the maximum coercive force Hc(max) and the minimum coercive force Hc(min) defined as (Hc(max)-Hc(min)) / Hc(min)×100(%) using the flat surface. It should be noted that the coercive force can be evaluated using a vibrating sample magnetometer (VSM: Vibrating Sample Magnetometer) or the like. In the case of low coercive force, a coercive force below 0.1Oe can also be measured by using a low magnetic field unit. The direction in the flat surface is changed relative to the direction of the measuring magnetic field for measurement.

[0070] It should be noted that "having a coercive force difference" means that when the coercive force is measured by applying a magnetic field along the 360-degree direction within the flat surface, there is a direction in which the coercive force is maximum and a direction in which the coercive force is minimum. For example, when the coercive force is measured by changing the direction at intervals of 22.5 degrees relative to the 360-degree angle within the flat surface, when a coercive force difference occurs, that is, an angle at which the coercive force becomes larger and an angle at which the coercive force becomes smaller, it is expressed as "having a coercive force difference". Figure 6 Schematic diagram showing the direction of measuring the coercive force by changing the direction at intervals of 22.5 degrees with respect to the 360-degree angle within the flat surface of the flat magnetic metal particle in the magnetic wedge of the first embodiment. Figure 6 In the figure, the flat surface of the flat magnetic metal particle is illustrated as a plane viewed from above.

[0071] By having a coercive force difference within the flat surface, the minimum coercive force value is reduced compared to the isotropic case with almost no coercive force difference, which is preferred. In a material having magnetic anisotropy within a flat surface, the coercive force has a difference depending on the direction within the flat surface, and the minimum coercive force value is reduced compared to the magnetic isotropic material. This reduces the hysteresis loss and improves the magnetic permeability, which is preferred. Figure 6 Flat magnetic metal particles 10 and flat surfaces 6 are shown.

[0072] In addition, the flat magnetic metal particles have a magnetic metal phase containing at least one first element selected from the group consisting of Fe, Co and Ni. It should be noted that the flat magnetic metal particles contain Fe and Co, and the amount of Co is preferably greater than 10 atomic % and less than 60 atomic % relative to the total amount of Fe and Co, and is further preferably contained in an amount of greater than 10 atomic % and less than 40 atomic %. This makes it easy to impart a large magnetic anisotropy appropriately, and the above-mentioned magnetic properties are improved, so it is preferred. In addition, the Fe-Co system easily achieves high saturation magnetization, so it is preferred. Furthermore, by making the composition range of Fe and Co fall within the above range, a higher saturation magnetization can be achieved, which is preferred.

[0073] Elements can be easily analyzed by EDX (Energy Dispersive X-ray spectroscopy), ICP (Inductively Coupled Plasma) emission spectroscopy, or the like.

[0074] The flat magnetic metal particles preferably contain at least one non-magnetic metal selected from the group consisting of Mg, Al, Si, Ca, Zr, Ti, Hf, Zn, Mn, Ba, Sr, Cr, Mo, Ag, Ga, Sc, V, Y, Nb, Pb, Cu, In, Sn, and rare earth elements. Thus, the thermal stability and oxidation resistance of the flat magnetic metal particles can be improved. Among them, Al and Si are particularly preferred because they are easily dissolved in Fe, Co, and Ni, which are the main components of the flat magnetic metal particles, and contribute to improving thermal stability and oxidation resistance.

[0075] It should be noted that in order to induce magnetic anisotropy, there is also the following method: the crystallinity of the flat magnetic metal particles is amorphized as much as possible, and magnetic anisotropy is induced in one direction in the plane by using magnetic field and strain. In this case, it is ideal to make the flat magnetic metal particles as easy to amorphize as possible. From this point of view, the magnetic metal contained in the flat magnetic metal particles preferably includes at least one additive element selected from B (boron), Si (silicon), Al (aluminum), C (carbon), Ti (titanium), Zr (zirconium), Hf (hafnium), Nb (niobium), Ta (tantalum), Mo (molybdenum), Cr (chromium), Cu (copper), W (tungsten), P (phosphorus), N (nitrogen), Ga (gallium), and Y (yttrium).

[0076] It is preferred that the difference between the atomic radius of at least one first element selected from the group consisting of Fe, Co, and Ni is large. In addition, it is preferred that the negative value of the mixing enthalpy of at least one first element selected from the group consisting of Fe, Co, and Ni and the added element becomes large. In addition, it is preferred that the multi-element system is formed by a total of more than three elements including the first element and the added element. In addition, semi-metallic added elements such as B and Si are easy to amorphize because the crystallization rate slows down, so it is beneficial if they are mixed into the system.

[0077] From the above viewpoints, B, Si, P, Ti, Zr, Hf, Nb, Y, Cu and the like are preferred, and among them, it is more preferred that the additive element contains any one of B, Si, Zr, Hf, and Y. As an example, it is preferred that the first element of the magnetic metal phase contains Fe and Co, and that Si and B are contained as the additive element.

[0078] Furthermore, the total amount of the additional element is preferably 0.001 atomic % or more and 80 atomic % or less, more preferably 5 atomic % or more and 80 atomic % or less, and further preferably 10 atomic % or more and 40 atomic % or less, relative to the total amount of the first element and the additional element.

[0079] It should be noted that the greater the total amount of the aforementioned added elements, the easier it is to amorphize and impart magnetic anisotropy, so it is preferred (i.e., it is preferred from the perspective of low loss and high magnetic permeability), but on the other hand, the ratio of the magnetic metal phase decreases, so the saturation magnetization decreases, which is not preferred in this regard. Based on the above situation, it is important to comprehensively consider high saturation magnetization, low loss, high magnetic permeability, etc. to select the composition and the amount of added elements.

[0080] The inclusion phase contains at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F). This is because the electrical resistance can be increased. The resistivity of the inclusion phase is preferably higher than the resistivity of the flat magnetic metal particles. This can reduce the eddy current loss of the flat magnetic metal particles. Since the inclusion phase exists surrounding the flat magnetic metal particles, it is possible to improve the oxidation resistance and thermal stability of the flat magnetic metal particles, which is preferred. Among them, the inclusion phase containing oxygen is more preferred from the perspective of high oxidation resistance and high thermal stability. The inclusion phase also plays the role of mechanically bonding the flat magnetic metal particles, so it is also preferred from the perspective of high strength.

[0081] The inclusion phase preferably contains a resin. As the resin, a thermoplastic resin, a thermosetting resin, a polyester resin, a vinyl ester resin, a polyethylene resin, a polystyrene resin, a polyvinyl chloride resin, a polyvinyl butyral resin, a polyvinyl alcohol resin, a polybutadiene resin, a Teflon (registered trademark) resin, a polyurethane resin, a cellulose resin, an ABS resin, a nitrile rubber, a styrene-butadiene rubber, a silicone resin, other synthetic rubbers, natural rubber, an epoxy resin, a phenolic resin, an allyl resin, a polybenzimidazole resin, an amide resin, a polyimide resin, a polyamide-imide resin, a bismaleimide resin, or a copolymer thereof can be used.

[0082] In order to achieve high thermal stability, the inclusion phase preferably contains silicone resin, polyimide resin, imide resin, bismaleimide resin with high heat resistance. Epoxy resin, phenolic resin, polyester resin are commonly used resins with high heat resistance and high strength, and are preferred.

[0083] In addition, the inclusion phase preferably contains at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenolic resins, epoxy resins, and silicone resins. In addition, the weight increase rate after exposure to the atmosphere at 120°C for 30 minutes and exposure to the atmosphere at room temperature for 1 week is preferably 1% or less, more preferably 0.1% or less.

[0084] In addition, the water absorption rate of the resin contained in the inclusion phase as specified in ISO 62:1999 (JIS K7209:2000) is preferably 1% or less, and more preferably 0.1% or less. In order to improve the strength, it is preferred that the inclusion phase also contains materials such as FRP (Fiber-Reinforced Plastics) obtained by mixing fibers such as glass fiber, aramid fiber, carbon fiber, Zylon fiber, polyethylene fiber, and boron fiber. By the above method, the flat magnetic metal particles and the inclusion phase are firmly bonded, and mechanical properties such as thermal stability, strength, and toughness are easily improved.

[0085] By surrounding the flat magnetic particles with the inclusion phase, the oxidation resistance is excellent and the magnetic properties are not easily degraded due to oxidation of the flat magnetic metal particles, which is preferred. It should be noted that the type of the resin can be identified by IR (Infrared Spectroscopy), NMR (Nuclear Magnetic Resonance), etc.

[0086] Bismaleimide resins are preferred because they can be molded at a relatively low temperature (e.g., below 180°C) during molding, and can therefore be molded using a commonly used low-temperature hot press apparatus. In addition, as properties after molding, high thermal stability and excellent mechanical properties can be achieved, so they are preferred. Furthermore, it is easy to compound (join) with flat magnetic metal particles, and it is also easy to achieve excellent mechanical properties such as thermal stability, strength, and toughness as a composite material, so it is preferred. In addition, the inclusion phase easily surrounds the flat magnetic particles, and it is not easy for the magnetic properties to deteriorate due to oxidation of the flat magnetic metal particles, so it is preferred.

[0087] The bismaleimide resin preferably has a glass transition temperature of 250° C. or higher. This is preferred because thermal stability, strength, and the like are improved.

[0088] The bismaleimide resin preferably includes 4,4'-diphenylmethane bismaleimide, phenylmethane maleimide, m-phenylene bismaleimide, bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 1,6'-bismaleimide-(2,2,4-trimethyl)hexane, 2,2'-diallyl bisphenol A, 4 ,4'-diphenyl ether bismaleimide, 4,4'-diphenyl sulfone bismaleimide, 1,3-bis(3-maleimide phenoxy)benzene, 1,3-bis(4-maleimide phenoxy)benzene, bis(3-ethyl-5-methyl-4-maleimide phenyl)methane, 2,2'-bis[4-(4-maleimide phenoxy)phenyl]propane, etc. (Since these monomers are polymerized to make bismaleimide resins, it is preferred to include the above substances in the form of monomers). As a result, thermal stability, strength, etc. are improved, which becomes preferred.

[0089] In addition, the curing agent for curing the monomer preferably includes 4,4'-diaminodiphenylmethane, diaminodiphenyl ether, diaminodiphenyl sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, o,o'-diallylbisphenol A, etc. However, the curing agent may be other types as long as it can appropriately cure the monomer.

[0090] As a preferred combination of a monomer and a curing agent, for example, 4,4'-diphenylmethane bismaleimide and 4,4'-diaminodiphenylmethane can be cited. In addition, when 4,4'-diphenylmethane bismaleimide and 4,4'-diaminodiphenylmethane are included, the ratio of 4,4'-diphenylmethane bismaleimide to 4,4'-diaminodiphenylmethane is preferably 1 to 3, and more preferably about 2. The above ratio is preferred because thermal stability, strength, etc. are improved.

[0091] The molecular weight of the inclusion phase is preferably 100 to 1000. This is preferred because thermal stability, strength, and the like are improved.

[0092] The polyimide resin preferably contains a repeating unit represented by the following chemical formula (1).

[0093]

[0094] In the chemical formula (1), R preferably includes any of the structures of biphenyl, triphenyl and tetraphenyl. R' preferably represents a structure having at least one aromatic ring in the structure.

[0095] Furthermore, as the polyimide resin, it is more preferable to have the structural formula (2) or (3) below.

[0096]

[0097] Figure 7 FIG. 1 is a schematic diagram of a magnetic wedge according to the present embodiment. Figure 7 As shown in the figure, the cross-section is not limited to a simple rectangular parallelepiped shape (rectangular), but may be a trapezoidal, hexagonal, convex, etc. The closer the magnetic wedge is to the gap surface between the rotor and the stator, the more the efficiency of the rotating electrical machine is improved. Therefore, from this point of view, the trapezoidal, convex, and hexagonal shapes are more preferable than the rectangular shape.

[0098] In addition, from the perspective of "a shape that makes it easy to improve the efficiency of the rotating electrical machine and to easily introduce magnetic flux to the magnetic wedge side", the trapezoidal type and the convex type are more preferable than the hexagonal type. On the other hand, from the perspective of ease of manufacturing and high reliability of mechanical properties, thermal properties, etc. as a material, the rectangular type is most preferred, followed by the trapezoidal type and the hexagonal type. In this sense, the trapezoidal type is easy to be arranged close to the gap surface between the rotor and the stator, and the magnetic flux is easily introduced to the magnetic wedge side by utilizing the trapezoidal shape, which is easy to manufacture and easy to improve the reliability of mechanical properties, thermal properties, etc. as a material, so it is very preferred.

[0099] It should be noted that, regardless of the shape, three mutually orthogonal or perpendicular axial directions are defined as the width direction, the thickness direction, and the length direction. The length direction of the magnetic wedge refers to the direction in which the length of the magnetic wedge is long. For example, when the shape of the target magnetic wedge is a substantially rectangular parallelepiped shape, the direction along the longest side of the substantially rectangular parallelepiped shape is determined as the length direction of the target magnetic wedge.

[0100] The thickness direction and width direction of the magnetic wedge refer to directions orthogonal to the length direction of the magnetic wedge. The thickness direction and width direction of the magnetic wedge can be distinguished as follows. In the case where the target magnetic wedge is set in a rotating electric machine, the target magnetic wedge is taken out from the inside of the rotating electric machine. Here, the rotation direction of the rotating electric machine is the width direction of the target magnetic wedge.

[0101] The thickness direction is a direction perpendicular to the width direction. On the other hand, when the target magnetic wedge is not set in a rotating electrical machine, the direction closest to the average orientation direction of the flat magnetic metal particles in the center of the cross section perpendicular to the length direction is the width direction. The thickness direction is a direction perpendicular to the width direction. It should be noted that, with respect to the cross section perpendicular to the length direction, the end face of the target magnetic wedge is avoided.

[0102] The cross section is cut perpendicularly to the longitudinal direction of the magnetic wedge to be used so as to have a length of at least 1 / 10 of the length of the magnetic wedge to be used. In addition, as the center of the cross section formed by cutting, for example, a region containing a plurality of flat magnetic metal particles is used at the geometric center of the cross section. Next, in the magnetic wedge to be used, the cross section formed by cutting is observed using an optical microscope, SEM, or TEM.

[0103] Then, for each flat magnetic metal particle observed in a cross section obtained by cutting, the rectangle with the smallest area among rectangles circumscribing each flat magnetic metal particle is identified, and the direction of the long side of the rectangle is measured as the orientation direction.

[0104] However, flat magnetic metal particles may include particles whose outlines are unclear during observation and difficult to evaluate. In other words, the outlines of particles may not be clearly determined in image analysis, and such particles are excluded from observation.

[0105] Figure 8 Schematic diagram of a magnetic wedge according to this embodiment. Figure 8 In the embodiment, the surface coating layer is present on at least a portion of the magnetic wedge. By covering the surface of the magnetic wedge with the surface coating layer, for example, excellent magnetic properties and electrical properties (high resistivity, etc.) can be obtained, and the excellent properties can be maintained without deteriorating the strength after the heat resistance test and the efficiency as a rotating electrical machine, which is preferred. By having the surface coating layer, oxidation of the flat magnetic metal particles and the flat magnetic metal surface particles contained in the magnetic wedge can be suppressed, and excellent magnetic properties (saturation magnetization, coercive force, and magnetic permeability) can be maintained, which is preferred.

[0106] The surface of the magnetic wedge in contact with the surface coating layer of the present embodiment may be smooth or rough. It should be noted that the surface roughness in contact with the surface coating layer means that the surface has irregularities (surface roughness), or the flat magnetic metal surface particles present near the surface in contact with the surface coating layer include particles that are not oriented in the width direction, or a portion of the length of the flat magnetic metal surface particles is arranged outside the contour average line (i.e., on the surface coating layer side).

[0107] Fig. 9 is another schematic diagram of the magnetic wedge according to this embodiment. Fig. 9 In the figure, a portion of the flat magnetic metal particles included in the magnetic wedge has a portion protruding from the magnetic wedge to the outside. The figure shows the flat magnetic metal particles existing near the contour line in the width direction in a cross section of the magnetic wedge perpendicular to its length direction and at the center of the length direction (hereinafter, the characteristics are defined based on this cross section). It should be noted that as a method for obtaining the cross section of the magnetic wedge perpendicular to its length direction and at the center of the length direction, the method is not limited as long as the size, contour line, etc. of the flat magnetic metal particles can be obtained. For example, observation is performed using a scanning electron microscope (SEM: Scanning Electron Microscopy) or an optical microscope or a transmission electron microscope (TEM: Transmission Electron Microscopy), etc., and observation is performed at any magnification. Here, the flat magnetic metal particles that exist closest to the contour line in the width direction are called flat magnetic metal surface particles. In addition, the contour average line in the width direction is an average line obtained by averaging the concave and convex state of the contour line in the width direction. The contour average line can be defined as the "average line" in the surface roughness measurement of JIS-B0601 (ISO-4287), etc.

[0108] In the magnetic wedge of the present embodiment, it is preferred that the flat magnetic metal surface particles of which 10% or more of the lengths are arranged outside the average line of the profile in the width direction are included. Furthermore, it is more preferred that the flat magnetic metal surface particles of which 10% or more of the lengths are arranged outside the average line of the profile in the width direction of the magnetic wedge are included in an amount of preferably 1% or more and 90% or less, more preferably 5% or more and 60% or less, and even more preferably 5% or more and 30% or less, relative to the total number of the flat magnetic metal surface particles present in the measured cross section.

[0109] The orientation angle of the flat magnetic metal surface particles, which have more than 10% of their length arranged on the outside of the average contour line of the width direction of the magnetic wedge, is preferably greater than 1 degree and less than 60 degrees, more preferably greater than 3 degrees and less than 45 degrees, and even more preferably greater than 3 degrees and less than 30 degrees, relative to the average contour line in the width direction.

[0110] In addition, as Figure 8 , Fig. 9 The surface roughness Ra of the contour line of the width direction of the magnetic wedge in the embodiment is 0.1 μm or more and 100 μm or less, more preferably 0.1 μm or more and 10 μm or less, and further preferably 1 μm or more and 10 μm or less. It should be noted that, preferably, the contour line of the width direction in the cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction (i.e., the surface in the width direction) preferably satisfies the surface roughness within this range, more preferably, the surface including the width direction and the length direction of the magnetic wedge satisfies the surface roughness within this range, and further preferably, any surface of the magnetic wedge satisfies the surface roughness within this range. It should be noted that the surface roughness Ra and its measuring method are defined by JIS-B0601 (ISO-4287).

[0111] In the case where the flat magnetic metal particles have a portion protruding outward on at least a portion of the surface of the magnetic wedge, the thickness of the surface coating layer is preferably greater than the average thickness of the flat magnetic metal surface particles, and more preferably greater than the average length of the flat magnetic metal particles. It is further preferably greater than the maximum length of the aforementioned flat magnetic metal particles. By having the above structure, the surface coating layer can be firmly fitted (bonded) with the magnetic wedge (anchoring effect) to protect the magnetic wedge, so it is preferred. As a result, the reliability of the material is improved, which is preferred. For example, since the resistivity can be greatly improved, when used as a magnetic wedge, electrical short circuits can be suppressed, and eddy current losses can be reduced and the efficiency of the rotating motor can be improved, so it is preferred. In addition, it is preferred that excellent properties can be maintained without deteriorating the strength after the heat resistance test and the efficiency as a rotating motor. In addition, it is preferred that the oxidation of flat magnetic metal particles and flat magnetic metal surface particles can be suppressed, and excellent magnetic properties (saturation magnetization, coercive force, magnetic permeability) can be maintained. In addition, by having the above structure (arrangement structure, number ratio, orientation angle, surface roughness, etc. of flat magnetic metal surface particles), it is possible to efficiently guide magnetic flux in the rotating electric machine, improve the magnetic permeability and efficiency of the rotating electric machine, so it is preferred. Regarding the magnetic permeability, the magnetic permeability in the direction between the width direction and the thickness direction of the magnetic wedge is improved, so it is preferred. In addition, the loss in the direction between the width direction and the thickness direction of the magnetic wedge is also reduced, which is also preferred.

[0112] The surface coating layer preferably contains an inorganic material such as an oxide, a carbide, a nitride, or a boride, or an organic material such as a resin, and more preferably contains a resin.

[0113] As the resin, thermoplastic resin, thermosetting resin, polyester resin, vinyl ester resin, polyethylene resin, polystyrene resin, polyvinyl chloride resin, polyvinyl butyral resin, polyvinyl alcohol resin, polybutadiene resin, Teflon (registered trademark) resin, polyurethane resin, cellulose resin, ABS resin, nitrile rubber, styrene-butadiene rubber, silicone resin, other synthetic rubber, natural rubber, epoxy resin, phenolic resin, allyl resin, polybenzimidazole resin, amide resin, polyimide resin, polyamide-imide resin, bismaleimide resin, or copolymers thereof can be used.

[0114] In order to achieve high thermal stability, the surface coating layer preferably contains a heat-resistant silicone resin, polyimide resin, imide resin, or bismaleimide resin. Epoxy resin, phenolic resin, and polyester resin are commonly used resins with high heat resistance and high strength and are preferred.

[0115] Furthermore, the surface coating layer preferably contains at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenolic resins, epoxy resins, and silicone resins.

[0116] It should be noted that, as mentioned above, the type of the resin can be identified by IR, NMR, etc. In addition, the surface coating layer is preferably a resin having a weight increase rate of 1% or less after exposure to the atmosphere at 120°C for 30 minutes and at room temperature for 1 week, and more preferably 0.1% or less. In addition, the water absorption rate specified in ISO 62:1999 (JIS K7209:2000) is preferably 1% or less, and more preferably 0.1% or less.

[0117] Preliminary investigations have revealed that, in a magnetic wedge formed of flat magnetic metal particles and an inclusion phase, especially when the inclusion phase is a resin, once water or moisture is absorbed, the weight increases, and mechanical properties such as strength and thermomechanical properties are easily deteriorated. In addition, once the flat magnetic metal particles absorb water or moisture, they also oxidize, the saturation magnetization and magnetic permeability decrease, and the loss increases, which is not preferred. Therefore, it is believed that it is effective to prevent the inclusion phase from contacting water or moisture as much as possible (to suppress the increase in weight).

[0118] As can be seen from the above, in this embodiment, by coating the surface of the magnetic wedge with a surface coating layer having low water absorption and hygroscopicity, the inclusion phase can be prevented from contacting water and moisture as much as possible. Therefore, as mentioned above, the surface coating layer is preferably a resin having a weight increase rate of 1% or less after exposure to the atmosphere at 120°C for 30 minutes and exposure to the atmosphere at room temperature for 1 week, and more preferably 0.1% or less. In addition, the water absorption rate specified in ISO 62:1999 (JIS K7209:2000) is preferably 1% or less, and more preferably 0.1% or less. It is further preferred that the surface coating layer comprises at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenolic resins, epoxy resins, and silicone resins, and the weight increase rate of the resin after exposure to the atmosphere at 120°C for 30 minutes and after exposure to the atmosphere at room temperature for 1 week is less than 1%, and the water absorption rate specified in ISO 62:1999 (JIS K7209:2000) is less than 1%. It is further preferred that the surface coating layer contains at least one resin selected from the group consisting of bismaleimide resin, polyimide resin, polyester resin, phenolic resin, epoxy resin, and silicone resin, and the weight increase rate of the resin after exposure to the atmosphere at 120°C for 30 minutes and after exposure to the atmosphere at room temperature for 1 week is 0.1% or less, and the water absorption rate specified in ISO 62:1999 (JIS K7209:2000) is 0.1% or less. By forming the above surface coating layer, mechanical properties such as strength and thermomechanical properties will not be deteriorated, and excellent properties can be maintained. In addition, since the oxidation of the flat magnetic metal particles is also suppressed, the saturation magnetization, magnetic permeability, and loss will not be deteriorated, and excellent properties can be maintained.

[0119] A method for manufacturing a magnetic wedge according to the present embodiment will be described. It should be noted that the manufacturing method is not particularly limited, and is described merely as an example.

[0120] The first step is a step of manufacturing a magnetic metal ribbon containing at least one first element selected from the group consisting of Fe, Co, and Ni. This step is a step of making a ribbon or a film using a film forming device such as a roll quenching device or a sputtering device. At this time, in the film forming method using the film forming device, it is desirable to form a film with uniaxial anisotropy in the film surface by film forming in a magnetic field, rotary film forming, etc.

[0121] The second step is a step of heat treating the magnetic metal strip at a temperature of 50°C to 800°C. It should be noted that the heat treatment atmosphere is preferably a vacuum atmosphere with a low oxygen concentration, an inactive atmosphere, or a reducing atmosphere, and more preferably and preferably, H 2(hydrogen), CO (carbon monoxide), CH 4 It is more preferable and more desirable to carry out the heat treatment in a magnetic field.

[0122] The third process is a process of crushing the heat-treated magnetic metal ribbon to produce flat magnetic metal particles. In this process, for example, crushing is performed using a crushing device such as a bead mill or a planetary grinder. It should be noted that the type of crushing device is not limited. For example, a planetary grinder, a bead mill, a rotary ball mill, a vibrating ball mill, a stirring ball mill (grinding machine), a jet mill, a centrifuge, or a method of combining a mill with a centrifugal separation can be listed.

[0123] It should be noted that, in the third step, not only is pulverization performed simply, but rolling can also be combined to make the thickness of the flat magnetic metal particles thinner. It should be noted that, in the case where a specified thickness has been formed by the second step, the process for rolling can be omitted. Here, rolling can be performed simultaneously, or rolling can be performed after pulverization, or pulverization can be performed after rolling. In this case, it is preferred that a device capable of applying a strong acceleration of gravity can be used, for example, a planetary grinder, a bead mill, a rotary ball mill, a vibrating ball mill, a stirring ball mill (grinder), a jet mill, a centrifuge, or a method of combining a mill with centrifugal separation, etc.

[0124] Ideally, the above-mentioned cutting, pulverizing, and rolling are performed (rolling is performed as necessary, and is not performed when not necessary), and the cutting, pulverizing, and rolling are repeated as needed to form flat magnetic metal particles with a specified thickness and aspect ratio.

[0125] In addition, it is desirable that the obtained flat magnetic metal particles be subjected to heat treatment to appropriately remove lattice distortion. The heat treatment at this time is preferably carried out at a temperature of 50°C or higher and 800°C or lower, as in the second step, and the heat treatment atmosphere is preferably a vacuum atmosphere with a low oxygen concentration, an inactive atmosphere, or a reducing atmosphere, and more preferably H 2 , CO, CH 4 In a reducing atmosphere such as above, the heat treatment is preferably carried out in a magnetic field.

[0126] Next, as the fourth step, the inclusion phase is mixed with magnetic metal particles to form a mixed powder of the inclusion phase and flat magnetic metal particles. Next, as the fifth step, the mixed powder of the inclusion phase and the magnetic metal particles is molded. In addition, heat treatment can be appropriately performed before or after the above steps. That is, heat treatment can be performed before or after molding or simultaneously with molding. In addition, heat treatment can be performed before or after processing. The heat treatment conditions are as described above. In addition, it is more preferred and more ideal to perform heat treatment in a magnetic field.

[0127] The fifth process preferably adopts a method of applying pressing pressure in a uniaxial direction, such as uniaxial pressing and hot pressing. If pressing pressure is applied in a uniaxial direction, the flat magnetic metal particles are easily stacked and oriented in the direction of application of the pressing pressure. Therefore, if it is a simple uniaxial pressing, the flat magnetic metal particles will be stacked and oriented in one direction along the direction of application of the pressing pressure, which is not preferred. Therefore, it is preferred to apply a magnetic field in a direction parallel to the direction of application of the pressing pressure when applying pressing pressure in a uniaxial direction. In addition, it is also preferred to magnetize the die punch during molding in a direction parallel to the direction of application of the pressing pressure. Through these, the flat magnetic metal particles become easy to move in a direction parallel to the direction of application of the pressing pressure. In addition, hot pressing is preferably performed after uniaxial pressing. In the case where the included phase is, for example, a thermosetting resin, it is preferred to adjust the hot pressing temperature and time during hot pressing and stop before the included phase solidifies. It should be noted that in hot pressing, it is more preferred to apply a magnetic field in a direction parallel to the direction of application of the pressing pressure while hot pressing.

[0128] In addition, during hot pressing, it is also preferred to reduce or release the pressing pressure when the resin softens or melts. Regarding the hot pressing temperature, it is preferably carried out at a temperature of 50°C or more and 1000°C or less, and more preferably 50°C or more and 800°C or less. The larger the applied magnetic field, the more preferred, preferably 1 kOe or more, and more preferably 10 kOe or more. The pressing pressure is preferably 1 MPa or more and 100 MPa or less, and more preferably 1 MPa or more and 10 MPa or less.

[0129] Then, it is preferred to perform heat treatment while applying a magnetic field in a direction parallel to the direction of application of the pressing pressure to completely solidify it. Regarding the heat treatment temperature, it is preferably performed at a temperature of 50°C or more and 1000°C or less, and more preferably at a temperature of 50°C or more and 800°C or less. The larger the applied magnetic field, the more preferred, preferably 1 kOe or more, and more preferably 10 kOe or more.

[0130] Here, by adjusting the hot pressing temperature and time, the "ratio of the flat magnetic metal surface particles whose length is 10% or more arranged outside the average line of the contour in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles" can be adjusted. For example, in the case where it is desired to increase the "ratio of the flat magnetic metal surface particles whose length is 10% or more arranged outside the average line of the contour in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles", it can be adjusted by lowering the hot pressing temperature or shortening the hot pressing time. Conversely, in the case where it is desired to reduce the "ratio of the flat magnetic metal surface particles whose length is 10% or more arranged outside the average line of the contour in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles", it can be adjusted by raising the hot pressing temperature or extending the hot pressing time. It should be noted that even in the case where the inclusion phase is a thermoplastic resin or an oxide having a softening point, the same magnetic wedge can be manufactured by making an effort in the molding process. That is, the same magnetic wedge can be manufactured regardless of the type of the inclusion phase. For example, during hot pressing, when the resin softens and melts, the same magnetic wedge can be manufactured by reducing or releasing the pressing pressure, applying a magnetic field in a direction parallel to the direction of application of the pressing pressure, or lowering the temperature in this state to solidify it.

[0131] Next, in the sixth step, a surface coating layer is formed on the surface of the formed magnetic wedge. In this step, an inorganic material or an organic material is coated on the surface of the magnetic wedge. The coating method is not particularly limited. When coating an organic material such as a resin, it is also preferable to coat it by an impregnation method, a dipping method, etc., or to press it by hot pressing or the like after coating, depending on the situation. When coating an inorganic material, it is also preferable to coat it by a gas phase method, a liquid phase method such as a sol-gel, etc., or to press it by hot pressing or the like after coating, depending on the situation. In addition, it is also preferable to perform a heat treatment after coating to form a strong coating layer.

[0132] When measuring the coercive force based on direction in a plane parallel to the flat surface of the flat magnetic metal particles of the magnetic wedge, the coercive force is measured by changing the direction at intervals of 22.5 degrees with respect to an angle of 360 degrees in the plane.

[0133] By having a coercive force difference in the aforementioned plane of the magnetic wedge, the minimum coercive force value becomes smaller than the isotropic case with almost no coercive force difference, which is preferable. In a material having magnetic anisotropy in a plane, the coercive force is made different depending on the direction in the plane, and the minimum coercive force value becomes smaller than the magnetic isotropic material. This reduces the hysteresis loss and improves the magnetic permeability, which is preferable.

[0134] The larger the ratio of the coercive force difference based on the direction in the plane parallel to the flat surface of the flat magnetic metal particles possessed by the magnetic wedge, the better, and preferably 1% or more. More preferably, the ratio of the coercive force difference is 10% or more, further preferably, the ratio of the coercive force difference is 50% or more, and further preferably, the ratio of the coercive force difference is 100% or more. The ratio of the coercive force difference mentioned here is defined as (Hc(max)-Hc(min)) / Hc(min)×100(%) using the maximum coercive force Hc(max) and the minimum coercive force Hc(min) in the flat surface.

[0135] It should be noted that the coercive force can be simply evaluated using a vibrating sample magnetometer (VSM) or the like. In the case of low coercive force, a coercive force of 0.1 Oe or less can also be measured by using a low magnetic field unit. The measurement is performed by changing the direction of the magnetic field in the aforementioned plane of the magnetic wedge (in the plane parallel to the flat surface of the flat magnetic metal particle) relative to the direction of the measurement magnetic field.

[0136] When calculating the coercive force, the value obtained by dividing the difference between the magnetic fields at two points intersecting the horizontal axis (magnetic fields H1 and H2 where magnetization is zero) by 2 can be used (that is, it can be calculated as coercive force = |H2-H1| / 2).

[0137] As described above, according to the present embodiment, the magnetic wedge is a magnetic wedge for a rotating electric machine, and the magnetic wedge has a plurality of flat magnetic metal particles, an inclusion phase, and a surface coating layer exists on at least a portion of the surface of the magnetic wedge. Thus, a magnetic wedge having excellent electrical properties, excellent heat resistance (electrical properties, magnetic properties, mechanical properties), etc. can be provided. In addition, it is further preferred that the magnetic wedge has flat magnetic metal particles, and the flat magnetic metal particles have the above-mentioned structure (the arrangement structure of the flat magnetic metal surface particles, the number ratio, the orientation angle, the surface roughness, etc.), and it is preferred because it can efficiently guide the magnetic flux in the rotating electric machine, improve the magnetic permeability and the efficiency of the rotating electric machine. In addition, by using the flat magnetic metal particles having the above-mentioned structure, the surface coating layer (anchoring effect) can be firmly formed, the reliability of the material can be further improved, and more excellent heat resistance (electrical properties, magnetic properties, mechanical properties) can be achieved, so it is preferred.

[0138] (Second embodiment)

[0139] The rotating electrical machine of this embodiment includes the magnetic wedge of the first embodiment. Therefore, the contents overlapped with those of the first embodiment are omitted. In this specification, the rotating electrical machine is a concept including a motor, a generator, and an electric generator that performs the functions of both a motor and a generator as required.

[0140] Fig.10 This is an example of a radial gap type motor according to the present embodiment. The radial gap type motor includes a rotor and a stator which is arranged to face the rotor with a predetermined gap in the radial direction. Fig.10 In the embodiment, the rotor is arranged inside the stator, but it may be arranged outside. The rotor includes a rotor core and a shaft, and is supported in a rotatable manner. On the other hand, the stator includes a stator core, a field coil inserted in a slot of the stator core, and a magnetic wedge held in a wedge groove at an opening of the slot. Fig.10 An example in which the magnetic wedges of the first embodiment are arranged is shown, but the present invention is not limited thereto. In the case of a radial gap type rotating electrical machine, the stator is arranged relative to the rotor at a predetermined interval in the radial direction, so the "gap surface" is a surface parallel to the cylindrical surface centered on the rotating axis of the rotor. Therefore, the radial direction is a direction perpendicular to the gap surface, and the axial direction and the rotation direction are directions parallel to the gap surface. Fig.10 Flat magnetic metal particles 10 , inclusion phases 20 , magnetic wedges 100 , a rotating electrical machine 200 , a rotor 210 , a stator 220 , a coil 230 , a gap surface 240 , and core teeth 250 are shown.

[0141] By configuring the magnetic wedge of the first embodiment, it is possible to suppress leakage flux and reduce the harmonic loss generated on the rotor surface. In addition, since the magnetic flux passing through the gap increases, the torque of the radial gap type motor increases. By either or both of the above loss reduction effect and torque increase effect, high efficiency can be achieved.

[0142] The radial gap motor may be any of a motor having a conductor on the rotor (induction motor), a motor having a permanent magnet (permanent magnet motor), and a motor having a magnetic body (reluctance motor).

[0143] Fig.11 This is an example of an axial gap type motor of the present embodiment. The axial gap type motor has a rotor and a stator arranged relative to the rotor with a predetermined gap in the axial direction, and the stator has a stator core, a field coil inserted in the slot of the stator core, and a magnetic wedge held in the wedge groove of the slot opening. By configuring the magnetic wedge of the present embodiment, the increase of leakage flux can be suppressed and the reduction of high-order harmonic loss generated on the surface of the rotor can be achieved. In addition, since the magnetic flux passing through the gap increases, the torque of the axial gap type motor increases. Through the above method, high efficiency can be achieved. Fig.11In the embodiment, the rotor is arranged between two stators, but it may be arranged on one side or both sides of a stator. In the case of an axial gap type rotating electric machine, since the stator is arranged relative to the rotor at a predetermined interval in the axial direction, the "gap surface" is a surface orthogonal to the rotation axis of the rotor. Therefore, the axial direction is a direction perpendicular to the gap surface, and the rotation direction and radial direction are directions parallel to the gap surface. Fig.11 Flat magnetic metal particles 10 , an inclusion phase 20 , a magnetic wedge 100 , a rotating electrical machine 200 , a rotor 210 , a coil 230 , a gap surface 240 , core teeth 250 , a stator 270 , and a shaft 280 are shown.

[0144] Fig.12 : is a schematic diagram showing an example of a generator of the present embodiment. The generator generally has a rotor that accommodates an excitation coil in a slot of a rotor core (in addition, a rotor that uses a permanent magnet as an excitation source may be used), and a stator that accommodates an armature coil in a slot of a stator core, so that the rotor rotates and an excitation current flows into the excitation coil, thereby generating power in the armature coil. The rotor includes a rotor core, a field coil inserted in a slot of the rotor core, and a magnetic wedge held in a wedge groove at an opening of the slot, and is supported by a bearing in a rotatable manner. By configuring the magnetic wedge of the present embodiment, the increase in leakage flux can be suppressed and the higher harmonic loss generated on the surface of the stator can be reduced. In addition, since the amount of magnetic flux that passes through the gap and interlinks with the armature coil increases, the power generation voltage caused by the armature coil increases. By the above method, high efficiency can be achieved. Fig.12 In the embodiment, the magnetic wedges are arranged at the slot opening of the rotor core, but they may be arranged at the slot opening of the stator core. In addition, the figure shows a winding type generator in which the rotor has an excitation coil, but it may also be a permanent magnet type generator in which the rotor has a permanent magnet. In this case, the magnetic wedges are arranged at the slot opening of the stator core. Fig.12 Flat magnetic metal particles 10 , inclusion phases 20 , magnetic wedges 100 , a rotating electrical machine 200 , a rotor 210 , a stator core 222 , a field coil 232 , an armature coil 234 , a gap surface 240 , and core teeth 250 are shown.

[0145] A linear motor is a flat plate-shaped structure obtained by developing a radial gap type motor, so the magnetic wedge of the present invention can also be applied to a linear motor. That is, the stator includes a stator core and a field coil inserted in a slot of the stator core, and the magnetic wedge can be provided at the slot opening. Fig.13: is a schematic diagram showing an example of a linear motor of the present embodiment. In the linear motor, the moving direction of the active element, the direction at right angles to the moving direction of the active element, and the direction perpendicular to the stator correspond to the rotation direction, axial direction, and radial direction of the radial gap type motor, respectively. By configuring the magnetic wedge of the present embodiment, the increase of leakage flux can be suppressed and the reduction of high-order harmonic loss generated on the surface of the active element can be achieved. In addition, since the magnetic flux passing through the gap increases, the thrust of the linear motor is improved. By the above method, high efficiency can be achieved. Fig.13 Flat magnetic metal particles 10 , an inclusion phase 20 , a magnetic wedge 100 , a stator 220 , a coil 230 , a gap surface 240 , a core tooth 250 , and a moving element 290 are shown.

[0146] As described above, according to the rotary electric machine of this embodiment, the increase of leakage magnetic flux caused by the use of magnetic wedges can be suppressed, and the pulsation of magnetic flux distribution on the surface of the core can be effectively alleviated, so that high efficiency can be achieved. It should be noted that the slot shape of the rotary electric machine of this embodiment can be a semi-closed slot (or semi-closed slot), preferably an open slot (or open slot). In this case, the high-order harmonic loss can be greatly reduced, which is preferred.

[0147] The rotating electric machine of this embodiment can be applied to transportation systems such as railways, electric vehicles, and hybrid vehicles, social systems such as elevators and air conditioners, industrial systems such as robots, pumps, compressors, and blowers, energy systems such as thermal generators, hydroelectric generators, wind generators, nuclear power generators, and geothermal generators, and home appliances such as washing machines, and can achieve high efficiency of the system. In particular, large-capacity machines for industrial use generally have slots as the slot shape, so it is preferable to have the magnetic wedge of the first embodiment. In addition, active motors for railways use type-wound coils based on the need to withstand high voltages and vibrations, and the slot shape is slotted, so it is preferable to have the magnetic wedge of the first embodiment.

[0148] For railways, since the loss of rotating electric machines accounts for about half of the power consumption when the railway is running, the effect of improving efficiency by reducing the loss of rotating electric machines is very large. In addition, for electric vehicles and hybrid vehicles, the efficiency of the active motor can be improved by using the magnetic wedge of the first embodiment, thereby increasing the cruising range.

[0149] Among generators, a great effect can be expected for a hydroelectric generator, particularly a variable speed pumped storage generator. In addition, a great effect can also be expected for a wind power generator.

[0150] Example

[0151] Hereinafter, Examples 1 to 15 will be described in more detail while comparing Comparative Example 1.

[0152] (Example 1)

[0153] First, a Fe-Co-Si-B (Fe70Co30B25(atomic%)-4wt%Si) thin strip was prepared using a single-roll quenching device. 2 The obtained flat magnetic metal particles are mixed with a polyester resin and molded. Then, hot press molding is performed to completely cure the resin to produce a magnetic wedge. At this time, there are no flat magnetic metal surface particles whose length is more than 10% arranged outside the average line of the contour in the width direction of the magnetic wedge. Then, the polyester resin is coated as a surface coating layer. It should be noted that the thickness of the surface coating layer is greater than the average thickness of the flat magnetic metal surface particles, the weight increase rate of the surface coating layer after exposure to the atmosphere at 120°C for 30 minutes and after exposure to the atmosphere at room temperature for 1 week is less than 1%, and the water absorption rate specified in ISO 62:1999 (JIS K7209:2000) is less than 1%.

[0154] (Example 2)

[0155] The process was substantially the same as in Example 1 except that a bismaleimide-based resin was used as the type of the surface coating layer.

[0156] (Example 3)

[0157] The process was substantially the same as in Example 1 except that a polyimide-based resin was used as the type of the surface coating layer.

[0158] (Example 4)

[0159] The surface coating layer was made of phenolic resin, and the other components were substantially the same as in Example 1.

[0160] (Example 5)

[0161] The surface coating layer was made of epoxy resin, and the other aspects were substantially the same as in Example 1.

[0162] (Example 6)

[0163] The surface coating layer was made of silicone resin, and the other components were substantially the same as in Example 1.

[0164] (Example 7)

[0165] In Example 1, flat magnetic metal particles are mixed with a polyester resin, and when molding is performed (when pressing pressure is applied in a uniaxial direction), a magnetic field is applied in a direction parallel to the direction in which the pressing pressure is applied. Then, hot press molding is performed. During hot press molding, the hot press temperature and time are adjusted and the molding is stopped before solidification occurs. Then, heat treatment is performed while applying a magnetic field in a direction parallel to the direction in which the pressing pressure is applied, so that the particles are completely solidified to produce a magnetic wedge. It should be noted that by adjusting the hot press temperature and time, the ratio of flat magnetic metal surface particles having a length of more than 10% arranged to the outside of the average contour line in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles is adjusted (30% in this Example 7). Then, the polyester resin is coated as a surface coating layer. It should be noted that it is confirmed that the thickness of the surface coating layer is greater than the average thickness of the aforementioned flat magnetic metal surface particles, the weight increase rate of the aforementioned surface coating layer after exposure to the atmosphere at 120°C for 30 minutes and after exposure to the atmosphere at room temperature for 1 week is less than 1%, and the water absorption rate specified in ISO 62:1999 (JIS K7209:2000) is less than 1%.

[0166] (Example 8)

[0167] The process was substantially the same as in Example 7 except that a bismaleimide-based resin was used as the type of the surface coating layer.

[0168] (Example 9)

[0169] The process is substantially the same as in Example 7 except that a polyimide-based resin is used as the type of the surface coating layer.

[0170] (Example 10)

[0171] The surface coating layer was made of phenolic resin, and the other aspects were substantially the same as those of Example 7.

[0172] (Example 11)

[0173] The surface coating layer was made of epoxy resin, and the other aspects were substantially the same as those of Example 7.

[0174] (Example 12)

[0175] The surface coating layer was made of silicone resin, and the other aspects were substantially the same as those of Example 7.

[0176] (Example 13)

[0177] The hot pressing temperature and time were adjusted so that the ratio of the flat magnetic metal surface particles having at least 10% of their length arranged outside the average contour line in the width direction of the magnetic wedge to the total number of the flat magnetic metal surface particles was 1%, and the method was substantially the same as Example 7 except that the ratio was 1%.

[0178] (Example 14)

[0179] The hot pressing temperature and time were adjusted so that the ratio of the flat magnetic metal surface particles having at least 10% of their length arranged outside the average contour line in the width direction of the magnetic wedge to the total number of the flat magnetic metal surface particles was 90%, and the method was substantially the same as Example 7 except that the ratio was 90%.

[0180] (Example 15)

[0181] The hot pressing temperature and time were adjusted so that the ratio of the flat magnetic metal surface particles having at least 10% of their length arranged outside the average contour line in the width direction of the magnetic wedge to the total number of the flat magnetic metal surface particles was 95%, and the method was substantially the same as Example 7 except that the ratio was 95%.

[0182] (Comparative Example 1)

[0183] The procedure was substantially the same as in Example 1 except that the polyester resin surface coating layer was not formed.

[0184] In Table 1, regarding the magnetic wedge of the present embodiment (Examples 1 to 15), the presence / absence of a surface coating layer, the type of the surface coating layer (limited to the case where there is a surface coating layer), and the ratio of flat magnetic metal surface particles having 10% or more of their length arranged outside the average line of the contour in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles are shown together with Comparative Example 1.

[0185] Table 2 shows the resistivity, resistivity after the heat resistance test, magnetic permeability, and strength of the magnetic wedges (Examples 1 to 15) according to the present embodiment together with Comparative Example 1.

[0186] (1) Resistivity: The DC resistivity of the surface of the magnetic wedge in the length direction and the width direction was measured and expressed as a ratio to the DC resistivity of the sample of Comparative Example 1 (=DC resistivity of the evaluation sample / DC resistivity of Comparative Example 1).

[0187] (2) Resistivity after heat resistance test: For the evaluation sample, the DC resistivity (DC resistivity of the surface of the magnetic wedge in the length direction and the width direction) was measured after heating at 180°C in the atmosphere for 100 hours (heat resistance test), and the ratio to the DC resistivity of the sample of Comparative Example 1 was expressed as (=DC resistivity of the evaluation sample after heating at 180°C in the atmosphere for 100 hours / DC resistivity of Comparative Example 1 after heating at 180°C in the atmosphere for 100 hours).

[0188] (3) Magnetic permeability after heat resistance test: For the evaluation sample, the magnetic permeability (magnetic permeability at 100 Hz in the direction between the width direction and the thickness direction of the magnetic wedge) after heating at 180°C in the atmosphere for 100 hours (heat resistance test) was measured and expressed as a ratio to the magnetic permeability of the sample of Comparative Example 1 after heating at 180°C in the atmosphere for 100 hours (=magnetic permeability of the evaluation sample after heating at 180°C in the atmosphere for 100 hours / magnetic permeability of Comparative Example 1 after heating at 180°C in the atmosphere for 100 hours).

[0189] (4) Strength after heat resistance test: For the evaluation sample, the flexural strength at 25°C after heating at 180°C in the atmosphere for 100 hours (heat resistance test) was measured, and the ratio was expressed as the flexural strength at 25°C after heating at 180°C in the atmosphere for 100 hours to the flexural strength of the sample of Comparative Example 1 at 25°C after heating at 180°C in the atmosphere for 100 hours (= flexural strength at 25°C after heating at 180°C in the atmosphere for 100 hours / flexural strength at 25°C after heating at 180°C in the atmosphere for 100 hours of Comparative Example 1).

[0190] Table 1

[0191]

[0192] Table 2

[0193]

[0194] As shown in Table 2, Examples 1 to 6 have excellent characteristics in terms of resistivity, resistivity after heat resistance test, magnetic permeability, and strength compared to Comparative Example 1. This is because the insulating surface coating layer is formed, which not only improves the resistivity of the surface of the magnetic wedge, but also protects the magnetic wedge during the heat resistance test. It can be seen that excellent characteristics can be maintained without deteriorating the resistivity, magnetic permeability, and strength after the heat resistance test. In addition, this effect is more significant by including 1% or more and 90% or less of the flat magnetic metal surface particles whose length is more than 10% arranged outside the average line of the outline in the width direction of the magnetic wedge relative to the total number of flat magnetic metal surface particles. It can be seen that in Examples 7 to 14, the flat magnetic metal surface particles whose length is more than 10% arranged outside the average line of the outline in the width direction of the magnetic wedge relative to the total number of flat magnetic metal surface particles are 1% or more and 90% or less, thereby achieving higher characteristics than 0% in Examples 1 to 6 and 95% in Example 15. That is, it can be seen that by "the flat magnetic metal surface particles having more than 10% of the length arranged on the outside than the average line of the outline in the width direction of the magnetic wedge are included in an amount of more than 1% and less than 90% of the total number of the flat magnetic metal surface particles", the resistivity, magnetic permeability and strength after the heat resistance test will be more excellent. In summary, if the surface coating layer is formed, the resistivity is improved, and the resistivity, magnetic permeability and strength after the heat resistance test are also improved. In particular, by "the flat magnetic metal surface particles having more than 10% of the length arranged on the outside than the average line of the outline in the width direction of the magnetic wedge are included in an amount of more than 1% and less than 90% of the total number of the flat magnetic metal surface particles", the effect becomes significant.

[0195] Several embodiments and examples of the present invention have been described, but these embodiments and examples are given as examples and are not intended to limit the scope of the invention. These new embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the gist of the invention. These embodiments and their variations fall within the scope and gist of the invention, and fall within the invention described in the claims and the scope of their equivalents.

[0196] It should be noted that the above implementation modes can be summarized as the following technical solutions.

[0197] (Technical Solution 1)

[0198] A magnetic wedge is a magnetic wedge for a rotating electric machine, wherein the magnetic wedge comprises a plurality of flat magnetic metal particles and an inclusion phase.

[0199] A surface coating layer exists on at least a portion of the surface of the magnetic wedge.

[0200] (Technical Solution 2)

[0201] The magnetic wedge according to claim 1, wherein the thickness of the surface coating layer is greater than or equal to the average thickness of the flat magnetic metal surface particles.

[0202] (Technical Solution 3)

[0203] The magnetic wedge according to claim 1 or 2, wherein the surface coating layer contains a resin.

[0204] (Technical Solution 4)

[0205] The magnetic wedge according to any one of claims 1 to 3, wherein the surface coating layer is a resin having a weight increase rate of 1% or less after exposure to an atmosphere of 120°C for 30 minutes and after exposure to an atmosphere of room temperature for one week.

[0206] (Technical Solution 5)

[0207] The magnetic wedge according to any one of claims 1 to 4, wherein the surface coating layer has a water absorption rate of 1% or less as specified in ISO 62:1999 (JIS K7209:2000).

[0208] (Technical Solution 6)

[0209] The magnetic wedge according to any one of claims 1 to 5, wherein the surface coating layer includes at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenolic resins, epoxy resins, and silicone resins.

[0210] (Technical Solution 7)

[0211] The magnetic wedge according to any one of claims 1 to 6, wherein in a cross section of the magnetic wedge perpendicular to its longitudinal direction and at the center of the longitudinal direction,

[0212] The plurality of flat magnetic metal particles include flat magnetic metal surface particles of which 10% or more of the length of the flat magnetic metal particles is arranged outside a mean line of the contour in the width direction of the magnetic wedge.

[0213] (Technical Solution 8)

[0214] A magnetic wedge according to any one of Technical Solutions 1 to Technical Solutions 7, wherein, in a cross section of the magnetic wedge perpendicular to its longitudinal direction and at the center of the longitudinal direction, flat magnetic metal surface particles having more than 10% of the length arranged on the outside than an average line of the contour in the width direction of the magnetic wedge are included in an amount of more than 1% and less than 90% of the total number of flat magnetic metal surface particles.

[0215] (Technical Solution 9)

[0216] A magnetic wedge according to any one of Technical Solutions 1 to Technical Solutions 8, wherein, in a cross section of the magnetic wedge perpendicular to its length direction and at the center of the length direction, flat magnetic metal surface particles having more than 10% of the length arranged on the outside than an average line of the contour in the width direction of the magnetic wedge have an orientation angle of more than 1 degree and less than 60 degrees relative to the average line of the contour in the width direction.

[0217] (Technical Solution 10)

[0218] The magnetic wedge according to any one of claims 1 to 9, wherein the surface roughness Ra of a contour line in the width direction of the magnetic wedge in a cross section perpendicular to the longitudinal direction and at the center in the longitudinal direction is 0.1 μm or more and 100 μm or less.

[0219] (Technical Solution 11)

[0220] The magnetic wedge according to any one of claims 1 to 10, wherein the inclusion phase exists between the plurality of flat magnetic metal particles and contains at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F).

[0221] (Technical Solution 12)

[0222] The magnetic wedge according to any one of claims 1 to 11, wherein the inclusion phase contains a resin.

[0223] (Technical Solution 13)

[0224] In the magnetic wedge according to any one of claims 1 to 12, the inclusion phase includes at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenolic resins, epoxy resins, and silicone resins.

[0225] (Technical Solution 14)

[0226] The magnetic wedge described in any one of Technical Solutions 1 to Technical Solutions 13, wherein the plurality of flat magnetic metal particles have a magnetic metal phase having an average thickness of 10 nm to 100 μm inclusive and containing at least one first element selected from the group consisting of Fe, Co and Ni, and an average value of a ratio of an average length within a flat surface to the thickness is 5 to 10,000 inclusive.

[0227] (Technical Solution 15)

[0228] A magnetic wedge according to any one of Technical Solutions 1 to 14, wherein at least a portion of the surface of the flat magnetic metal particles is covered with a coating layer having a thickness of 0.1 nm to 1 μm and containing at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F).

[0229] (Technical Solution 16)

[0230] The magnetic wedge according to any one of claims 1 to 15, wherein there is a coercive force difference based on a direction within the flat surface of the flat magnetic metal particle.

[0231] (Technical Solution 17)

[0232] The magnetic wedge according to any one of claims 1 to 16, wherein the magnetic wedge has a coercive force difference based on a direction in a plane parallel to the flat surface.

[0233] (Technical Solution 18)

[0234] A rotating electrical machine comprises the magnetic wedge described in any one of claims 1 to 17.

Claims

1. A magnetic wedge, which is a magnetic wedge of a rotating electrical machine, comprising a plurality of flat magnetic metal particles, an inclusion phase, A surface coating layer is present on at least a portion of the surface of the magnetic wedge.

2. The magnetic wedge according to claim 1, wherein: The thickness of the surface coating layer is equal to or greater than the average thickness of the flat magnetic metal surface particles.

3. The magnetic wedge according to claim 1, wherein: The surface coating layer contains a resin.

4. The magnetic wedge according to claim 1, wherein: The surface coating layer is a resin having a weight increase rate of 1% or less after exposure to air at 120° C. for 30 minutes and after exposure to air at room temperature for one week.

5. The magnetic wedge according to claim 1, wherein: The water absorption of the surface coating layer as specified in ISO 62:1999 or JIS K7209:2000 is 1% or less.

6. The magnetic wedge according to claim 1, wherein: The surface coating layer includes at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenolic resins, epoxy resins, and silicone resins.

7. The magnetic wedge according to claim 1, wherein: In a cross section of the magnetic wedge perpendicular to its length direction and at the center of the length direction, The plurality of flat magnetic metal particles include flat magnetic metal surface particles of which 10% or more of the length of the flat magnetic metal particles is arranged outside the average line of the contour in the width direction of the magnetic wedge.

8. The magnetic wedge according to claim 1, wherein: In a cross section of the magnetic wedge perpendicular to its longitudinal direction and at the center of the longitudinal direction, flat magnetic metal surface particles having more than 10% of the length arranged outside the average line of the contour in the width direction of the magnetic wedge are included in an amount of more than 1% and less than 90% relative to the total number of the flat magnetic metal surface particles.

9. The magnetic wedge according to claim 1, wherein: In a cross section of the magnetic wedge perpendicular to its longitudinal direction and at the center of the longitudinal direction, the orientation angle of the flat magnetic metal surface particles that are arranged more than 10% of the length on the outside than the average line of the contour in the width direction of the magnetic wedge is greater than 1 degree and less than 60 degrees relative to the average line of the contour in the width direction.

10. The magnetic wedge according to claim 1, wherein: The surface roughness Ra of the outline of the magnetic wedge in the width direction in a cross section perpendicular to the longitudinal direction and at the center in the longitudinal direction is 0.1 μm or more and 100 μm or less.

11. The magnetic wedge according to claim 1, wherein: The inclusion phase exists between the plurality of flat magnetic metal particles and contains at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N), and fluorine (F).

12. The magnetic wedge according to claim 1, wherein: The inclusion phase includes a resin.

13. The magnetic wedge according to claim 1, wherein: The inclusion phase includes at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenolic resins, epoxy resins, and silicone resins.

14. The magnetic wedge according to claim 1, wherein: The plurality of flat magnetic metal particles have an average thickness of 10 nm to 100 μm inclusive and include a magnetic metal phase containing at least one first element selected from the group consisting of Fe, Co, and Ni, and an average value of a ratio of an average length in a flat surface to the thickness is 5 to 10,000 inclusive.

15. The magnetic wedge of claim 1, wherein: At least a portion of the surface of the flat magnetic metal particle is covered with a coating layer having a thickness of 0.1 nm to 1 μm and containing at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N), and fluorine (F).

16. The magnetic wedge of claim 1, wherein: The flat magnetic metal particles have a coercive force difference depending on the direction within the flat surface.

17. The magnetic wedge of claim 1, wherein: There is a direction-dependent coercive force difference in a plane parallel to the flat surface. 18 . A rotating electrical machine comprising the magnetic wedge according to claim 1 .